Tension Mechanism Dynamic Analysis - Lukac, Michal; Brumercik, Frantisek; Krzywonos, Leszek; Drozdziel, Pawel (Communications - Scientific letters of the University of Zilina, 2014)
The aim of the presented article is to show how to create a mathematical model of the tension mechanism working by a spring motion generation and contacting a rigid body at the end of the motion.